2017
DOI: 10.33610/01229907.v22n23
|View full text |Cite
|
Sign up to set email alerts
|

Características de la mortalidad por enfermedad diarreica aguda en población menor de cinco años registrada en el sistema de Vigilancia en Salud Pública, Colombia 2008 - 2016

Abstract: Introducción: La enfermedad diarreica es una de las principales causas de mortalidad y morbilidad en la niñez en el mundo. Más de la mitad de esas muertes prematuras se deben a enfermedades que se podrían evitar o tratar si hubiera acceso a intervenciones simples y asequibles. El objetivo de este estudio es identificar las características de la mortalidad por enfermedad diarreica aguda en menores de cinco años registrada en el Sistema de Vigilancia en Salud Pública (Sivigila) en el periodo 2008 – 2016 Metodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…The deaths and sequelae rate derived from this type of accident ranged between 0.04% and 7.6%, and between 5% and 9% respectively, being limb loss the worst sequel occurring in the 6.3% of the accidents. 28 , 34 , 40–42 These findings were very similar to the reported by Leon-Nuñez et al 6 for the period 2008–2016 in Colombia. The decrease in the severity of the accidents may be associated with an increase in the antivenom provided to treat each classified envenomation, as explained below.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…The deaths and sequelae rate derived from this type of accident ranged between 0.04% and 7.6%, and between 5% and 9% respectively, being limb loss the worst sequel occurring in the 6.3% of the accidents. 28 , 34 , 40–42 These findings were very similar to the reported by Leon-Nuñez et al 6 for the period 2008–2016 in Colombia. The decrease in the severity of the accidents may be associated with an increase in the antivenom provided to treat each classified envenomation, as explained below.…”
Section: Resultssupporting
confidence: 86%
“…Considering the classification of the severity of the accident, the SIVIGILA figures showed that an average of 26.4%, 12.5%, and 10.5% of the mild, moderate and severe classified accidents respectively did not receive antivenoms ( Table 1 ). 28 , 34 , 40–42 , 51 A decrease in the number of patients that did not receive any antivenom was detected in the figures from Leon-Nuñez et al 6 for the period 2008–2016 in Colombia. Despite this decrease, the fact that envenomed patients still not receiving the specific treatment is especially concerning, and place people at a high risk of sequels or death, as supported by Otero et al 37 After using antivenoms, adverse reactions were reported in 7.5% of the individuals.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations